Compreendendo o papel da cooperação nos casos de afastamento do trabalho por motivo de doença - Santos, Jennifer Oliveira Amaro dos (2017)
According to the Annual Management Report of the Regional Reference Center on Workers' Health (a) of 2015 (City Hall of João Pessoa, 2015) in 2013 in the State of Paraíba, 5,016 notifications of occupational accidents were recorded, with 19 deaths, based on data presented in the Statistical Yearbook Of Social Security. It is even more problematic to think that such data only communicate about workers entering the formal market, governed by the Consolidation of Labor Laws (CLT) and who reported their accident through the Work Accident Notice, so that 53% of the population Economically Active (PEA) of the State of Paraíba is presented in the informal labor market and is not part of the official statistics of occupational accidents, and that are attended by the Unified Health System-SUS. Therefore, the main purpose of the present study was to understand the role of cooperation, or lack thereof, in the health / disease relationship in the work environment. In order to analyze the complex relationship between cooperation, health, work, illness and retirement due to illness, the Psychodynamics of Work was adopted as a theoretical contribution. With regard to the method, the qualitative approach was favored, making use of two instruments: a socio-demographic questionnaire and a semi-structured interview. Ten workers of both sexes ranging from 27 to 54 years old participated in this study. The data analysis was conducted through a hermeneutic approach from the Work Psychodynamics. It has been found that the emphasis on productivity and management by goals have generated competitiveness among workers, as well as the weakening of ties of solidarity in work environments, so that this individualism has generated illness and, in fact, it becomes necessary to discuss about The role of cooperation in the reality of sick leave. It was also observed that even in clear conditions of suffering, workers still point to recognition as a way of fighting for health, and their absence is a source of suffering and illness. It was also verified that the majority of the interviewees did not obtain benefit of the INSS, even with medical examinations that accounted for pathologies, which became even more problematic for cases of mental disorders. It was noted the cooperation of family and friends as a prime factor for the subject to remain fighting for his health.